What types of bondholders impede corporate innovative activities? - Iftekhar Hasan; Jonathan O Brien; Pengfei Ye (Bank of Finland, 2013)
This study investigates whether institutional bond blockholders (i.e., bond funds that hold more than 5% of a firm's outstanding bonds) impede firm innovative activities, and if they do, through which channels. We find that long-term bond blockholders do not discourage firms from conducting innovative activities. Short-term bond blockholders, however, significantly reduce both firm investments in R&D and the innovative quality of these investments. Furthermore, their negative impact is stronger than the negative impact of short-term stockholders. Our results cannot be fully explained by short-term bondholders' a priori investment preferences and are robust to possible endogeneity concerns. Overall, they suggest that the option of the 'Wall Street walk' allows bondholders to exert considerable influence on firms' risk-taking decisions.
URN:NBN:fi:bof-20140807674
Keywords: G23; G31; 330; Bondholder; Innovation; Investment Horizon; Wall Street Walk